CNTFR rs41274853 and ACTN3 R577Xpolymor-phism are associated with weightlifting performance - Homma, H.; Kobatake, N.; Saito, M.; Mochizuki, Y.; Okamoto, T.; Nakazato, N.; Nishiyama, T.; Kikuchi, N. (The Journal of Physical Fitness and Sports Medicine, 2020)
[Aims] CNTFR rs41274853 polymorphism and ACTN3 R577X polymorphism are specifically expressed in skeletal muscle, which have been reported to be associated with muscle phenotypes, such as strength and power output. The purpose of present study was to determine the association between weightlifting performance (snatch, clean and jerk) and CNTFR rs41274853 and ACTN3 R577X poly-morphisms in weightlifters. [Methods] In present study, 165 weight-lifters (103 males and 62 females) and 338 control subjects (122 men and 216 women) were participated. Total DNA was extracted from saliva samples. Two gene polymorphisms were analyzed using the TaqMan probe method. Weightlifting performance was obtained by recording the best record for each participant in an official weightlift-ing competition by questionnaire. [Results] There was no significant difference of the frequency in CNTFR rs41274853 ACTN3 R577X polymorphisms between weightlifters and controls. The relative re-cord of snatch, clean and jerk, and total were significantly higher in CT+TT genotype than in the athletes with CC genotype (men: 3.44± 0.67kg vs 3.19 ± 0.55kg, p=0.038, women: 3.04 ± 0.38kg vs 2.77 ± 0.36kg, p=0.006). In the ACTN3 R577X polymorphism, athletes with RR genotype (192.1 ± 30.4 kg) recorded significantly higher performance than RX+XX genotype (171.7 ± 24.9 kg) in women weightlifters (p=0.002). [Conclusions] Our results suggested that the CNTFR rs41274853 CT+TT genotype and ACTN3 R577X RR genotype are associated with athletic performance in weightlifters.